مستوى معرفة معلمي الطور الابتدائي بذوي صعوبات التعلم - جريوي.زينب; زكري,نرجس (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية البحث عن مستوى معرفة معلمي المرحلة الابتدائية بذوي صعوبات التعلم وذلك من خلال قياس معرفتهم بماهية صعوبات التعلم والفرق بينها وبين المشاكل التعليمية المتداخلة معها ومعرفتهم بأنواع صعوبات التعلم، وكذا طرق وآليات الكشف والاحالة والتكفل. ولتحقيق هذه الأهداف المسطرة تم استخدام استبيان مستوى معرفة المعلمين بذوي صعوبات التعلم صمم خصيصا لهذه الدراسة، وتكونت عين الدراسة من (81) معلم ومعلمة، كما تم استخدام المنهج الاستكشافي وتوصلت الدراسة إلى أن مستوى معرفة المعلمين بذوي صعوبات التعلم هي دون المتوسط حيث أن مستوى معرفة المعلمين بماهية صعوبات التعلم وانواعها أقل من المتوسط، ومستوى معرفتهم بالفرق بين صعوبات التعلم والمشاكل التعليمية المتداخلة معها منخفض وأيضا مستوى معرفتهم بطرق واليات الكشف منخفض، كما أن مستوى معرفتهم بالإحالة والتكفل بذوي صعوبات التعلم هي دون المتوسط. Abstract : The current study aims to explore the level of knowledge of primary school teachers with learning disabilities by measuring their knowledge of what learning disabilities are and the difference between them and interrelated educational problems and their knowledge of the types of learning disabilities, as well as ways and means of detection, referral and support. To achieve this study, a teacher's level of knowledge questionnaire with learning disabilities, designed specifically for this study, was used (81) teachers, the exploratory curriculum was used and the study found that teachers' level of knowledge of learning difficulties is below average, as teacher's level of knowledge of what learning disabilities are and their types is below average. Their level of knowledge of the difference between learning disabilities and interrelated educational problems is low and their level of knowledge of detection methods and mechanisms is low. and their level of knowledge of referral and support with learning difficulties is below average.
Keywords: صعوبات تعلم; تأخر دراسي; learning disabilities; teacher; school delay; slow learning; detection